Representation Of Child Sexual Abuse and Dysfunctionality of Indian Upper Middle-Class Families in Mahesh Dattani’s Thirty Days in September - Dr. Shauli Mukherjee (Zien Journals, 2021)
One of his significant plays which deals with the complex issue of child sexual abuse in the Indian society is Thirty Days in September. The play treats the sensitive, and generally taboo issue of child sexual abuse, and most importantly, the wrapped-up subject of incest. It endeavours to lift the veil of silence which surrounds child sexual abuse and addresses the issue unflinchingly. It builds on the trauma of a woman protagonist, Mala Khatri, who lives with the haunting memories of her abused past. Her abuser - her uncle - subconsciously lives with her all the time, as a part of her dirty reflections
Keywords: Mahesh Dattani; child sexual abuse; unflinchingly; issue